2018
DOI: 10.1016/j.wombi.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery student reactions to workplace violence

Abstract: Clinical placements can impact on midwifery students' future careers. Universities need to prepare students for the possibility of workplace violence and arm them with appropriate strategies for safely dealing with it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…Of the twelve studies included in this integrative review, all discussed the prevalence of bullying and violence towards midwifery students in clinical settings, whilst undertaking their Bachelor of Midwifery degree ( Gillen et al., 2009 ; Steen 2011 ; Boyle and McKenna 2016 ; McKenna and Boyle 2016 ; Arundell et al., 2018 ; Hogan et al., 2018 ; Shapiro et al., 2018 ; Capper et al., 2020a ; Capper et al., 2020b ; Capper et al., 2020c ; Capper et al., 2021a ; Capper et al., 2021b ). Gillen et al.…”
Section: Resultsmentioning
confidence: 99%
“…Of the twelve studies included in this integrative review, all discussed the prevalence of bullying and violence towards midwifery students in clinical settings, whilst undertaking their Bachelor of Midwifery degree ( Gillen et al., 2009 ; Steen 2011 ; Boyle and McKenna 2016 ; McKenna and Boyle 2016 ; Arundell et al., 2018 ; Hogan et al., 2018 ; Shapiro et al., 2018 ; Capper et al., 2020a ; Capper et al., 2020b ; Capper et al., 2020c ; Capper et al., 2021a ; Capper et al., 2021b ). Gillen et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, the characteristics of violence and the responses of nursing students were unclear. Research found that midwifery students discussed the incident with acquaintance after a violence incident and few of them completed an incident report or received official debriefing [ 11 ]. Some students may worry about losing their job after the violence, while others do not trust the hospital staff.…”
Section: Introductionmentioning
confidence: 99%
“…When considering professionals' training, we need to reflect on the notion that midwife students can learn about how they might act violently while training because this occurs during their training [43]. At the same time, this violence is diluted in a sea of horizontal violence, which is neither reported nor made visible [44]. Too many activists worldwide in general, and in Spain in particular, continue to highlight that healthcare studies that contemplate the gender data gaps that exist for diseases and treatments and psychological processes, such as pregnancy, birth, or menopause, are still lacking [36].…”
Section: Discussionmentioning
confidence: 99%